2021
DOI: 10.1016/j.jaut.2021.102687
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection among autoimmune rheumatic disease patients: Data from an observational study and literature review

Abstract: The impact of COVID-19 infection in patients with autoimmune/auto-inflammatory rheumatic diseases (AARD) under immunomodulatory treatment has been a focus of interest during the SARS-CoV-2 pandemic. In this observational study, demographic data, disease related features and comorbidities, COVID-19 manifestations and outcome, as well as antibody responses to SARS-CoV-2 were recorded among 77 consecutive patients with underlying AARD infected by SARS-CoV-2. Analysis of data was performed using univariate and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 68 publications
(87 reference statements)
3
16
1
2
Order By: Relevance
“…Of note, hospitalisation and death rates in our unvaccinated patients were comparable to those described by a previous observational study examining COVID-19 outcomes in patients with SRD in our country. 14 As shown in figure 1, and in accordance with other reports, 8 9 about half of our patients got infected during the first 10 weeks after the second vaccine dose. Although it is well known that vaccine efficacy declines overtime, therefore most breakthrough infections would be expected to occur closer to the end of the observational period; it should be noted that temporal fluctuations of the viral load in the community, during spring 2021 in Greece, 15 explain our results.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, hospitalisation and death rates in our unvaccinated patients were comparable to those described by a previous observational study examining COVID-19 outcomes in patients with SRD in our country. 14 As shown in figure 1, and in accordance with other reports, 8 9 about half of our patients got infected during the first 10 weeks after the second vaccine dose. Although it is well known that vaccine efficacy declines overtime, therefore most breakthrough infections would be expected to occur closer to the end of the observational period; it should be noted that temporal fluctuations of the viral load in the community, during spring 2021 in Greece, 15 explain our results.…”
Section: Discussionsupporting
confidence: 92%
“…Predisposing factors for severe disease, hospitalisation, and COVID-19 related death of AARD patients were similar to the ones described in our work. 8 12 Furthermore, the same therapeutic agents which were described in our study led AARD patients with COVID-19 to severe outcome and death. Mortality of AARD patients from COVID-19 was also found to be comparable to the one in the general population 13 .…”
supporting
confidence: 67%
“…Our group conducted a prospective study exploring COVID-19 manifestations, outcomes, as well as antibody responses to SARS-CoV-2 among infected AARD patients. 8 It was shown that the majority of patients (68.8%) experienced a mild disease course, about a quarter (23.4%) required inpatient treatment, and the mortality rate was 1.2%. Regarding symptomatology, fatigue, low grade fever, respiratory, and musculoskeletal complaints were predominant in the clinical picture of these patients.…”
mentioning
confidence: 99%
“…The outcomes of COVID-19 in patients treated with biologic agents is a subject of intense investigation and evidence is accumulating rapidly. Data from the COVID-19 Global Rheumatology Alliance, among other, indicated that patients under RTX may carry an increased risk of serious disease [ 1 , 2 ]; this was confirmed recently in several registries [ 3 , 4 ] fueling concerns regarding the use of B cell depleting agents during the pandemic, especially in patients not yet vaccinated against COVID-19. Herein, we present a rare case of severe, protracted COVID-19 pneumonia in a patient with MCTD who was infected a few days following RTX treatment with a fatal outcome.…”
Section: Introductionmentioning
confidence: 98%